Setting up a transfusion laboratory for covid-19 samples: an experience from a new teaching hospital - Idris, Faridah; Wong, Ying Ying (Faculty of Medicine and Health Sciences, UPM, 2022)
University Putra Malaysia (UPM) Teaching Hospital or Hospital Pengajar UPM (HPUPM) is a new 400-bed teaching hospital that started operations in 2019 and initially did not manage COVID-19 patients. However, due to a surge of COVID-19 patients in Malaysia in 2021, HPUPM needs to manage COVID-19 patients in various categories, including those needing intensive care. This paper explored the experience of setting up the transfusion laboratory for COVID-19 samples within a short notice, including the development of the protocol, challenges, and lessons learnt during the whole process.